2016
DOI: 10.1038/srep27144
|View full text |Cite
|
Sign up to set email alerts
|

The CebE/MsiK Transporter is a Doorway to the Cello-oligosaccharide-mediated Induction of Streptomyces scabies Pathogenicity

Abstract: Streptomyces scabies is an economically important plant pathogen well-known for damaging root and tuber crops by causing scab lesions. Thaxtomin A is the main causative agent responsible for the pathogenicity of S. scabies and cello-oligosaccharides are environmental triggers that induce the production of this phytotoxin. How cello-oligosaccharides are sensed or transported in order to induce the virulent behavior of S. scabies? Here we report that the cellobiose and cellotriose binding protein CebE, and MsiK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 45 publications
4
95
1
Order By: Relevance
“…scabies . We generated a bglC null mutant (Δ bglC ) by replacing orf scab57721 with the apramycin resistance cassette, as performed previously for cebR , cebE and msiK (Francis et al ., ; Jourdan et al ., ). Semi‐quantitative analysis by high‐performance liquid chromatography (HPLC) revealed that the Δ bglC /Δ 57721 mutant produced only 37% and 9% of the thaxtomin levels produced by the wild‐type strain when cultivated in liquid minimal medium (MM) with (Glc) 2 or (Glc) 3 as sole carbon source, respectively (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…scabies . We generated a bglC null mutant (Δ bglC ) by replacing orf scab57721 with the apramycin resistance cassette, as performed previously for cebR , cebE and msiK (Francis et al ., ; Jourdan et al ., ). Semi‐quantitative analysis by high‐performance liquid chromatography (HPLC) revealed that the Δ bglC /Δ 57721 mutant produced only 37% and 9% of the thaxtomin levels produced by the wild‐type strain when cultivated in liquid minimal medium (MM) with (Glc) 2 or (Glc) 3 as sole carbon source, respectively (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…As we demonstrated that bglC/BglC is induced by cellooligosaccharides and displays BG activity against (Glc) 2 and (Glc) 3 , we finally assessed whether the catabolic activity of BglC influenced the production levels of thaxtomin A and, as a consequence, the virulence of S. scabies. We generated a bglC null mutant (DbglC) by replacing orf scab57721 with the apramycin resistance cassette, as performed previously for cebR, cebE and msiK (Francis et al, 2015;Jourdan et al, 2016). Semi-quantitative analysis by high-performance liquid chromatography (HPLC) revealed that the DbglC/D57721 mutant produced only 37% and 9% of the thaxtomin levels produced by the wild-type strain when cultivated in liquid minimal medium (MM) with (Glc) 2 or (Glc) 3 as sole carbon source, respectively ( Fig.…”
Section: Inactivation Of Bglc Results In Reduced Thaxtominmentioning
confidence: 99%
See 3 more Smart Citations